Identification Customer Needs Of Trolley Product - Nurjannah Nurjannah; Agung Indrianto (Sustainable Environmental and Optimizing Industry Journal, 2022)
Trolley is a means of transportation that is often used in warehouses to move goods from one place to another. Driven trains are widely used because they are economical and do not require too much maintenance. However, in its use there are still obstacles such as piles that are too high so that goods fall, there is no control over the stroller so it cannot stop suddenly. The redesign of the trolley requires information related to customer needs, so this study aims to identification customer needs for the trolley using the Quality Function Deployment (QFD) method. The customer needs obtained include a trolley that is safe to use, a comfortable trolley, a trolley that is easy to fold, a trolley that is easy to carry, and a strong trolley material. The dominant technical characteristic based on QFD results is the type of material and the thickness of the trolley material is 135.00. The specifications of the trolley are 70 x 50 x 67 cm, plate iron material type, hollow iron frame material type, iron pipe handle material type, rubber wheel material type, have handbrake, and fastening rubber rope.